2000
DOI: 10.1080/03946975.2000.10531135
|View full text |Cite
|
Sign up to set email alerts
|

Surface activity in the mudskipper,Periophthalmus waltoniKoumans 1941 in relation to prey activity and environmental factors

Abstract: Surface activity and foraging behaviour of the carnivorous mudskipper Periophthalmus waltoni Koumans 1941, was investigated in relation to environmental conditions on the mudflats of Sulaibikhat Bay, Kuwait. Fish occupied several burrows systems within a 2-3 m 2 home range. Foraging activity was largely independent of environmental conditions only being inhibited by high wind speeds and surface temperatures below 15 °C. Hunting forays were longer than other surface activity, but once prey was caught, the mudsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Simultaneous with the shift in diet the relative gut length increases. The manifestation of both changes in the barred mudskipper contradicts the general guild‐based pattern of gut lengths (Piet, 1998), while changes in other gobiid fishes are consistent with the pattern (Geevarghese, 1983; Clayton & Snowden, 2000; Yang et al 2003).…”
Section: Discussionmentioning
confidence: 79%
“…Simultaneous with the shift in diet the relative gut length increases. The manifestation of both changes in the barred mudskipper contradicts the general guild‐based pattern of gut lengths (Piet, 1998), while changes in other gobiid fishes are consistent with the pattern (Geevarghese, 1983; Clayton & Snowden, 2000; Yang et al 2003).…”
Section: Discussionmentioning
confidence: 79%
“…g . Periophthalmus waltoni Koumans 1941; Clayton & Snowden, ). It appears unlikely that the moderate seasonal changes in rainfall in the study area can significantly affect the observed interspecific habitat segregation, at the spatial scales of the measured environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Periophthalmus living in semi-arid climates are known to perform seasonal migrations to wetter areas during dry periods (e.g. Periophthalmus waltoni Koumans 1941;Clayton & Snowden, 2000). It appears unlikely that the moderate seasonal changes in rainfall in the study area can significantly affect the observed interspecific habitat segregation, at the spatial scales of the measured environmental variables.…”
Section: H a B I Tat S E G R E G At I O Nmentioning
confidence: 91%
“…Observations were always made on the exposed substratum and under different tidal conditions: (1) ±2 h around predicted and observed low tide or, when visible, at a distance of >10 m from the water's edge (low tide): under these conditions, the fish distribution was assumed to be unaffected by water movement, and (2) near the water's edge, during flood and ebb tides. No data were collected when a plot was influenced by rain or wind (Clayton & Snowden, 2000).…”
Section: Methodsmentioning
confidence: 99%